KINERJA DOMPET DHUAFA DI KOTA MAKASSAR - Usman Usman (Jurnal Berita Sosial, 2018)
Optimizing the Performance of South Sulawesi Dompet Dhuafa Against Poverty Alleviation in Makassar City. This study aims to determine the efforts made Dompet Dhuafa in poverty alleviation in the city of Makassar and to find out the problems experienced by Dompet Dhuafa in poverty alleviation in the city of Makassar.This type of research is a qualitative research with research approach used is the approach of sociology and communication approach is the data source of this research is the employees of Dompet Dhuafa Sulsel. Furthermore, data collection methods used are observation, interview, documentation and reference search. Processing techniques and data analysis is done through four stages: data reduction, data presentation, comparison analysis techniques and conclusions drawing.The results of this study indicate that there are several efforts made by Dompet Dhuafa in poverty alleviation in Makassar City are: Looking for private donors and CSR funds of companies in Makassar. The collected funds are used in the fields of education, health and economic empowerment through independent institutions or free courses for the unemployed so as to better develop the skills they have. Keywords